Moral Rights in Media Work in Light of the Copyright Law and Related Rights in Iraqi Kurdistan - Fawzi, Saman (Journal of Legal and Political Studies, 2016)
One of the manifestations of the developed countries compared to other developing countries is the culture of respecting the moral rights of others, and protecting these rights via effective legislations. This lead to more innovations and creations in all life aspects, such as media. From this point our research has come to existence “intellectual rights in media- in the light of the authors rights and other related rights to it in Iraqi Kurdistan Region, number (17) for the year 2013.if we look for the most important media businesses and activities, which are protected by the author right law, that prohibit the publish by other media methods unless having the authority from their owners or through a specific legal procedure. We also researched in other media businesses and activities that exceptionally protected through the law for some reasons that got priority of the author’s right protection. Finally, we went through the protection tools of the media moral rights and its types either civil or criminal or precaution ones, and for the sake of strengthen the moral rights in media field, suggestions and recommendation were given. Thus we went through the in independence of this career, which in the outcome lead to develop the society and strengthen the democracy in it.
Keywords: Moral Rights; intellectual rights; civil or criminal or precaution; Media